The Role of Digital Transformation and Transformational Leadership in Enhancing Employee Performance in the Industry 4.0 Era - Amroni; Hodi; Murthada; Helmi Akmal Fauzan; Riesna Apramilda (SAJMR : Southeast Asian Journal of Management and Research, 2026)
This study aims to analyze the role of digital transformation and transformational leadership in enhancing employee performance in the Industry 4.0 era. This research employs a Systematic Literature Review (SLR) approach using the PRISMA framework to identify, evaluate, and synthesize relevant studies published between 2019 and 2025. A total of selected articles from reputable and Scopus-indexed journals were analyzed. The findings indicate that digital transformation significantly improves employee productivity, efficiency, and adaptability through the integration of advanced technologies. Transformational leadership also plays a critical role in motivating employees, fostering innovation, and facilitating organizational change. Furthermore, the integration of digital transformation and transformational leadership creates a stronger and more sustainable impact on employee performance. This study contributes to the development of organizational strategies in adapting to the challenges of the Industry 4.0 era.